Optimization of plastic spur gear of gear box in a single stage - Tauviqirrahman, Mohammad; Wijaya, Yosua; Ismail, Rifky; Paryanto, P. (AIP Conference Proceedings, 2024)
The most common failure in plastic spur gear is the less strength in the operation condition. This study aims to optimize the plastic spur gear in a single stage to improve the strength of spur gear. In this study, finite element analysis (FEA) is performed on gears under cyclic loading. The greatest stresses are sustained in each step of cyclic loading, and crucial spots are determined. The modeling of the gears is done in Solidworks software, while the FEA (Ansys Static Structural) is used for the analysis. Ansys Static Structural is used in this research to model the stresses and load impact on the gear. Shape optimization is done in this study to find the best couple from increasing fillet root radius and face width. The simulation results show that based on the optimization of plastic spur gear, an increase in the strength by 12,673% with increasing fillet radius of the root and an increase in the strength by 32.43% with the optimized shape design (by increasing fillet radius and face width) are obtained.
CRIS-Team Scopus Importer:2024-09-20